2006 14th Mediterranean Conference on Control and Automation 2006
DOI: 10.1109/med.2006.328835
|View full text |Cite
|
Sign up to set email alerts
|

Planning Optimal Motions for a DELTA Parallel Robot

Abstract: This article deals with the problem of planning optimal trajectories for a DELTA parallel robot. The planning process consists of searching for a motion ensuring the accomplishment of the assigned task, minimizing a cost function and satisfying various constraints inherent to the robot kinematics and dynamics. This problem is treated via (i) an adequate parameterization of the operational coordinates of the mobile platform and (ii) the use of the sequential quadratic programming method for solving the resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In order to analyze the control performance of the designed robust PID controller in the time domain, a trajectory planning was implemented using the modified trapezoidal acceleration curve method, in which acceleration and jerk is small for pick-and-place task [28,29]. Table III shows the waypoints of the track for the control simulation of the Delta parallel robot.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In order to analyze the control performance of the designed robust PID controller in the time domain, a trajectory planning was implemented using the modified trapezoidal acceleration curve method, in which acceleration and jerk is small for pick-and-place task [28,29]. Table III shows the waypoints of the track for the control simulation of the Delta parallel robot.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Due to the closed kinematic structure, Delta robots present better performance in accuracy, rigidity and payload capacity over their serial counterparts. All these advantages make this robot a good platform in many areas of engineering [1215]. However, the Delta robot system is a kind of nonlinear, strong coupling system with time-varying parameters, and traditional controllers cannot provide a satisfactory control performance.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the algorithm was capable of determining the required velocity profiles and corresponding actuator efforts in a computationally-efficient manner even in the case of highly complex dynamic constraints. Afroum et al [12] presented an approach for planning the trajectories of a 3-DOF DELTA parallel robot in which the operational coordinates of the moving platform were parameterized within the task space and the optimal solutions were derived using a sequential quadratic programming method. However, these studies only considered the single objective trajectory planning of PKMs.…”
Section: Introductionmentioning
confidence: 99%